Diagenetic history of the Miocene Surma Group sandstones from the Eastern Fold Belt of the Bengal Basin. Issue 7 (1st June 2022) - Sayem, Abu Sadat Md.; Rahman, M. Julleh Jalalur; Abdullah, Rashed; Azim, K.M. Riawsat
Highlights: The Eastern Fold Belt (EFB) is one of the key petroleum provinces in the Bengal Basin. This study explores the diagenetic history of the Surma Group sandstones in the EFB. Matrix, ductile grains and poikilotopic calcite cement influence the reservoir quality. The dominant control is the effects of compaction. Abstract: The Eastern Fold Belt (EFB) of the Bengal Basin remains an under-explored petroleum province in Bangladesh. Interbedded sandstones and shales of the Miocene Surma Group are thought to host hydrocarbon accumulations in EFB. The diagenetic history and their controls on sandstone reservoir quality and distribution are largely unknown in this region. Therefore, this paper aims to improve the understanding of diagenetic processes and their impacts on reservoir quality in the Surma Group sandstones. Thin section petrography, Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD) analysis have all been used to this end. The results of this study show that the sandstones are very fine- to medium- grained, moderately to moderately well-sorted, matrix- rich and dominantly sublitharenites. The principle diagenetic minerals/cements are calcite, authigenic chlorite, illite/illite–smectite, minor quartz cement, and minor kaolinite. Poikilotopic calcite cement drastically reduces the porosity and permeability down to 0%. Authigenic chlorite rims along quartz grain prevent quartz overgrowth, which acts to preserve porosity. The primary porosity (0–22%, average 9%) is by far the most dominant porosity in the Miocene Surma Group reservoirs, with burial enhanced secondary porosity caused by dissolution. Reservoir quality is mainly controlled by mechanical and ductile grain compaction and calcite cement.